Clinical evaluation tools and AACN essentials in Baccalaureate Nursing Education - Speer, Kathleen (1987)
The problem of the study was to determine concepts of nursing in clinical evaluation tools. The two research questions were: (1) Did the clinical evaluation tools exhibit the concepts used in the Essentials of College and University Education for Nursing by the American Association of Colleges of Nursing, and (2) What was the percent of inclusion of the Essentials in clinical evaluation tools nationally and in the four regions, South, West, North Atlantic, and Midwest? The sample for the study was the 186 NLN accredited baccalaureate nursing programs in the U.S. responding, which comprised 49.87% of the total number of schools. The methodology for the study utilized content analysis. All items from the 186 clinical evaluation tools were analyzed for similarity to one of the AACN essentials. The total number of items by region in each AACN category was determined. A national average and ranking was also determined for each category. The results of the analysis of data showed that the number one category for the nation and all four regions related to professional knowledge, judgment and skill needed to practice responsibly and accountably. The other top four ranking categories related to planning nursing care, assessment and physical examination, education of individuals and groups, and implementation of nursing care. One conclusion drawn was there is consistency and uniformity by all schools of nursing in evaluating professional judgment and skills. Professionalism and professional judgment is one of the basic differences between baccalaureate and associate degree nursing education. The items in this concept may be more concrete, therefore easier to evaluate. A concern is that 40% of the items pertained to professional judgment and 60% pertained to professional behavior. The area of evaluating professional judgment needs to be strengthened.